The impact of COVID-19 on national hockey league players` return to play - Lyng, J.; Morissette, M.; Ogborn, D.; Leiter, J.; MacDonald, P.; Longstaffe, R. (The Physician and Sportsmedicine, 2024)
Objective Evaluate the on-ice performance and return to play (RTP) rate following COVID-19 for National Hockey League (NHL) players during the 2020-21 season.